1975
DOI: 10.1111/j.1432-1033.1975.tb09894.x
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Antigen of Shigella dysenteriae Type 3. Structural Features of Specific Polysaccharide Chain

Abstract: On mild acid hydrolysis of lipolysaccharide from Shigella dysenteriae, type 3 the O‐specific polysaccharide (hapten) was obtained which appeared to be acidic branched hexosaminoglycan. The repeating unit of this polysaccharide represents a pentasaccharide composed of two d‐galactose residues, N‐acetyl‐d‐galactosamine, d‐glucose and unidentified acidic component. On the basis of methylation analysis, periodate oxidation, partial acid hydrolysis and chromic anhydride oxidation it is concluded that the structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1975
1975
1986
1986

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…Paper chromatography and paper electrophoresis followiiig acid hydrolysis showed that the polysaccharide from E. coli 0124 consisted of glucose, galactose, galactosamine and an acidic component which had the same chromatographic mobility as the acidic coniponent found in Sh. dysenteriae type 3 [6]. The latter has recently been identified as 4-0-(1-carboxyethyl)-D-glucopyranose (glucolactilic acid) [7].…”
Section: Isolation and Characterization Of The 0-specific Polj~sacchamentioning
confidence: 99%
See 4 more Smart Citations
“…Paper chromatography and paper electrophoresis followiiig acid hydrolysis showed that the polysaccharide from E. coli 0124 consisted of glucose, galactose, galactosamine and an acidic component which had the same chromatographic mobility as the acidic coniponent found in Sh. dysenteriae type 3 [6]. The latter has recently been identified as 4-0-(1-carboxyethyl)-D-glucopyranose (glucolactilic acid) [7].…”
Section: Isolation and Characterization Of The 0-specific Polj~sacchamentioning
confidence: 99%
“…In paper electrophoresis [6] The proton magnetic resonance spectrum of polysaccharide 11, recorded at I00 MHz (Fig. 3) exhibited signals of the C-methyl group of glucolactilic acid (6 = 1.4 ppm; 3 protons; J = 6 Hz; doublet), of the acetamido group of N-acetylgalactosamine (6 = 2.05 ppm; 3 protons; singlet) and five signals corresponding to five anomeric protons (4.40,4.50,4.76 ppm, doublet; J = 6 Hz; 4.94 ppm, doublet, J = 3 Hz; 5.06 ppm).…”
Section: Physical Characterizationmentioning
confidence: 99%
See 3 more Smart Citations